2014
DOI: 10.1007/s10803-014-2221-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Need for Personal Supports Among Workers with Autism Using an iPod Touch as an Assistive Technology: Delayed Randomized Control Trial

Abstract: Personal digital assistants (PDAs) are versatile task organizers that hold promise as assistive technologies for people with cognitive-behavioral challenges. This delayed randomized controlled trial compared two groups of adult workers with autism spectrum disorder (ASD) to determine whether the use of an Apple iPod Touch PDA as a vocational support improves work performance and reduces personal support needs on the job. Baseline data were collected on 50 adults with ASD who were beginning a vocational placeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 41 publications
1
87
0
13
Order By: Relevance
“…One study focused on describing the characteristics of people with autism who use residential services. Nine studies assessed the impact of interventions that included assistive technology (AT) [13,17,18,25,26,29,35,38,50]. Among the AT studies, six studied the use of AT to improve employment outcomes [13,17,18,25,26,29], one involved the use of a computer-based intervention for college students [35], one involved using AT to support the development of social skills [38], and one involved using AT to teach community shopping skills [50].…”
Section: Distribution Of Topics and Aimsmentioning
confidence: 99%
“…One study focused on describing the characteristics of people with autism who use residential services. Nine studies assessed the impact of interventions that included assistive technology (AT) [13,17,18,25,26,29,35,38,50]. Among the AT studies, six studied the use of AT to improve employment outcomes [13,17,18,25,26,29], one involved the use of a computer-based intervention for college students [35], one involved using AT to support the development of social skills [38], and one involved using AT to teach community shopping skills [50].…”
Section: Distribution Of Topics and Aimsmentioning
confidence: 99%
“…38 Some members may struggle more than others while learning their roles. New technology may be an effective tool to engage learners with ASD and achieve organizational objectives 23 while reducing high anxiety, 2 a variable that contributes to self-perceived performance deficiencies and, ultimately, poor job performance. 39 Participants reported that they learned from the training, felt engaged, and had fun, suggesting that their MTS experience increased their self-efficacy and learning, reduced anxiety, and helped manage task-related uncertainty.…”
Section: Research Objective Achievementmentioning
confidence: 99%
“…[18][19][20][21] The use of new technology for task-related training of newly hired ASDs remains virtually uninvestigated, although research found that ASD adults respond well to visual prompts, and one study suggested that ASD adults responded more favorably using an IPod Touch during their training. 22,23 The purpose of this exploratory study was twofold: (a) to evaluate if MTS strategies can positively impact the selfefficacy of ASD adults while learning a specific vocational task and (b) to observe and document the reactions, opinions, and emotional responses of ASD adults to MTS. Given previous research on other learning situations, and the theories of social learning, engagement, and organizational assimilation, self-efficacy of ASD adults should increase.…”
Section: Introductionmentioning
confidence: 99%
“…Barrierer for utnyttelse av teknologi kan vaere mangel på opplaering i bruk, og at teknologi generelt sett benyttes lite på arbeidsplassen (Bureau of Labor Statistics 2011). Introduksjon av forbrukerteknologi, kombinert med kunnskap om de mulighetene teknologien gir, og opplaering og tilpasning med veiledere som er positive og forståelsesfulle, er blitt pekt på som faktorer som fremmer utnyttelse av teknologi i arbeidslivet (Gentry, Kriner, Sima, McDonough & Wehman, 2015;Haugli, Maeland & Magnussen, 2011).…”
Section: Bakgrunn Og Kunnskapsstatusunclassified